The Role of Human Centromeric RNA in Chromosome Stability - Leclerc, Simon; Kitagawa, Katsumi (Frontiers in Molecular Biosciences, 2021)
Chromosome instability is a hallmark of cancer and is caused by inaccurate segregation of chromosomes. One cellular structure used to avoid this fate is the kinetochore, which binds to the centromere on the chromosome. Human centromeres are poorly understood, since sequencing and analyzing repeated alpha-satellite DNA regions, which can span a few megabases at the centromere, are particularly difficult. However, recent analyses revealed that these regions are actively transcribed and that transcription levels are tightly regulated, unveiling a possible role of RNA at the centromere. In this short review, we focus on the recent discovery of the function of human centromeric RNA in the regulation and structure of the centromere and discuss the consequences of dysregulation of centromeric RNA in cancer.